Adjustment of costly extra-group paternity according to inbreeding risk in a cooperative mammal. (3rd July 2015) - Nichols, Hazel J.; Cant, Michael A.; Sanderson, Jennifer L.
Lay Summary: Female-banded mongooses risk their lives to mate with rivals during pack "warfare." Data from wild banded mongooses reveal that 18% of pups are fathered by males from rival packs. These pups are less likely to be inbred are heavier and have higher survival chances than their within-pack counterparts. However, their mothers risk a lot to mate with extra-pack males; aggressive encounters between packs account for 20% of pup deaths and 12% of adult deaths. Abstract : Females of many animal species seek mating opportunities with multiple males, despite being able to obtain sufficient sperm to father their offspring from a single male. In animals that live in stable social groups, females often choose to mate outside their group resulting in extra-group paternity (EGP). One reason proposed to explain female choice for extra-group males is to obtain compatible genes, for example, in order to avoid inbreeding depression in offspring. The benefits of such extra-group paternities could be substantial if they result in fitter, outbred offspring. However, avoiding inbreeding in this way could be costly for females, for example, through retaliation by cuckolded males or through receiving aggression while prospecting for extra-group mating opportunities. We investigate the costs and benefits of EGP in the banded mongoose Mungos mungo, a cooperatively breeding mammal in which within-group mates are sometimes close relatives. We find that pups born to females that mate with extra-group males are more genetically heterozygous are heavier and are more likely to survive to independence than pups born to females that mate within their group. However, extra-group matings also involve substantial costs as they occur during violent encounters that sometimes result in injury and death. This appears to lead femalebanded mongooses to adaptively adjust EGP levels according to the current risk of inbreeding associated with mating within the group. For group-living animals, the costs of intergroup interactions may help to explain variation in both inbreeding rates and EGP within and between species.